Synthesis of Bis-1,2-Aryl-Biguanidino-Oxy, 3-Biguanidino Propane as Potential Antimalarial - Khatri, Dilip; Rajora, Sonal; Banu, Tahira; Talesara, G.L. (Asian Journal of Chemistry, 2010)
Various phthalimido-phthalimido-oxy, amino-amino-oxy, biguanidino-biguanidino-oxy and related derivatives of alkanes have been synthesized. For this purpose N-(allyl) phthalimide has been prepared and brominated to produce 2,3-dibromophthalimidopropane. This when condensed with N-hydroxy phthalimide, phthalimido, bis-phthalimido-oxypropane was resulted. Hydrolysis of above compound in HBr/AcOH acid produced3-amino 1,2-bis-amino-oxypropane tri-hydrobromide. This compound on condensation with substituted aryldicyandiamide gave various biguanidino-biguanidino- oxy derivative.